Socio-Structural Aspects of Globalization: Methodological Research Foundations - Evgeny G. Melnikov; Vladimir P. Miletskiy; Sergey D. Savin (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
The article examines the category of the global social structure and its position in the conceptual and categorical apparatus of modern sociological science. This category is characterized by a certain novelty and needs further theoretical development. The authors note and describe the concepts that form the basis of the society’s global social structure research from the perspective of the modern system approach, and consider its significance in the typology of social structures of society. A special place in the article is devoted to the levels of social structures, the study of theoretical concepts that constitute the foundation of methodological representations of the global social structure study. As methodological sources, the article uses works directly related to the concepts of global social structure and metastructure. The authors conduct a sociological analysis of the social system and social structure categories; identify the social structure levels according to the dialectics of individual, special and general cognition. The article discusses the possibilities of applying the main provisions of A. A. Bogdanov’s tectology as a method for sociological research of various modern social systems and structures types. The applicability of the globalization sociological apparatus within the framework of the sustainable development concept is considered. The study suggests that the global social structure should be considered in conjunction with new social formations, namely global social strata and institutions. However, but this requires further development of the conceptual and categorical apparatus.